Analysis of the fear of prophets Moses in the Quran: its Causes, its Implicational Outcomes (The International Journal of Educational Sciences and Arts, 2026)
This study analyzes the fear of Prphet Moses (musa) as it appear in the Quran, tracing its recurrent manifestations and identifying its racaurrent manifestations and identifying its causes, its theological and intellectual implications,and its educational outcomes in the course of the prophetic mission, the first section presents the main situations of fear in moses life from the incident of the Egyptian and  his departure from Egypt, to his fear at the moment of being commissioned with the prophethood and confronting Pharaoh, his fear when the staff turned into a serpent,and his fear when the sorcery of the magicians became evident highting the human of his faith and trust in God, and how the Quran safeguards the status of prophethood from any misunderstanding of weakness or cowardice, the second section discusses the difference between blmeworthay fear and praiseworthy fear,links this fear to the dimension of human nature and the rejection of  exaggeration, and shows that it is followed by hope and tranquility and crowned by complete trust in God, presenting it as a model for the believing human being in dealing with innate emotions not denying them, but redirecting them toward servitude and certainty, the study concludes that moses fear is an innate, human, and praiseworthy fear that leads to trust in God, not to doubt in the divine promise, and that it is consistently associated, in the Quranic context, with secuity and tranquility, reflecting a process of education and purification rather than weakness or deficiency in faith.
Keywords: Fear of Prophets Moses; the Quran-Analysis of Fear-Causes of Fear; TheologicaI Implication of Fear; Pedagogical Outcomes